AN ANALYSIS OF PHONOLOGY IN MINANGKABAU LANGUAGE - Fatimah Fatimah (Universitas Potensi Utama, 2018)
This study attempted to describe an analysis of phonology in Minangkabau Language. The purpose of the study was to describe the phonology in Minangkabau Language, types and distribution of diphthong and consonants and phonology form on the oral text of speakers in Padang and other regions such as Padang Panjang, Bukit Tinggi, and Sawah Lunto. The method of this study was library research by selecting and collecting some materials which were relevant to the subject matter. The data source of this study was oral text from speakers who lived in Padang and other places such as Padang Panjang, Bukit Tinggi and Sawah Lunto.